1999
DOI: 10.1074/jbc.274.36.25842
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of cAMP in Neurons and Astrocytes

Abstract: Mitogen-activated protein kinase (MAPK) activation provides cell type-specific signals important for cellular differentiation, proliferation, and survival. Cyclic AMP (cAMP) has divergent effects on MAPK activity depending on whether signaling is through Ras/Raf-1 or Rap1/ B-raf. We found that central nervous system-derived neurons, but not astrocytes, express B-raf. In neurons, cAMP activated MAPK in a Rap1/B-raf-dependent manner, while in astrocytes, cAMP decreased MAPK activity. Inhibition of MAPK in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
5

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(205 citation statements)
references
References 39 publications
11
189
5
Order By: Relevance
“…Nicotine was previously shown to induce mitogen-activated protein kinase (MAPK) signaling pathway in pheochromocytoma (PC12) cells via activation of protein kinase C/Raf/RSKII/CREB [52]. In the present study, we found that, in PFC, nicotine self-administration increased the expression of Rap1 guanine-nucleotide-exchange factor activated by cAMP (EPAC; 1.93-fold increase), which mediates the activation of B-raf in neurons [56,9]. The involvement of Rap family of rasrelated GTPases in response to nicotine administration was further accentuated by the changes observed in two additional genes involved in the Rap signaling pathway, namely Rap2A (1.66-fold increase in PFC) and MR-GEF (0.71-fold decrease in PFC and NAs).…”
Section: Region-specific Transcriptional Response To Chronic Nicotinesupporting
confidence: 48%
“…Nicotine was previously shown to induce mitogen-activated protein kinase (MAPK) signaling pathway in pheochromocytoma (PC12) cells via activation of protein kinase C/Raf/RSKII/CREB [52]. In the present study, we found that, in PFC, nicotine self-administration increased the expression of Rap1 guanine-nucleotide-exchange factor activated by cAMP (EPAC; 1.93-fold increase), which mediates the activation of B-raf in neurons [56,9]. The involvement of Rap family of rasrelated GTPases in response to nicotine administration was further accentuated by the changes observed in two additional genes involved in the Rap signaling pathway, namely Rap2A (1.66-fold increase in PFC) and MR-GEF (0.71-fold decrease in PFC and NAs).…”
Section: Region-specific Transcriptional Response To Chronic Nicotinesupporting
confidence: 48%
“…It has been proposed that epinephrine, acting on nociceptors, produces mechanical hyperalgesia through three different signaling pathways involving 1) cAMP-dependent PKA; 2) epsilon isozyme of PKC; and 3) extracellular signal-regulated kinases 1 and 2 (1,20). It has been demonstrated that the latter two pathways may also be initiated by the accumulation of cAMP (8,35). However, recent pharmacological and electrophysiological studies have reported the presence of ␤-adrenoceptor-mediated cAMP-independent signaling pathways (38); for example, the ␤ 3 -adrenoceptor-induced relaxation of gastrointestinal smooth muscle has been proposed to be mediated through the activation of a delayed rectified K ϩ channel (15).…”
Section: Discussionmentioning
confidence: 99%
“…The downstream targets of GTP-loaded Rap1 are in most cases not well characterized, with one exception: the cytoplasmic kinase B-Raf has been implicated as a Rap1-target in many studies (Ohtsuka et al, 1996;Vossler et al, 1997;York et al, 1998;Dugan et al, 1999;Czyzyk et al, 2000;Grewal et al, 2000;Schmitt and Stork, 2000;and others). This leads to activation of the MAPK/Erk kinases and subsequent activation of the transcription factor Elk-1.…”
Section: C3gmentioning
confidence: 99%